2006
DOI: 10.1124/jpet.105.099937
|View full text |Cite
|
Sign up to set email alerts
|

Thienorphine Is a Potent Long-Acting Partial Opioid Agonist: A Comparative Study with Buprenorphine

Abstract: A strategy in the development of new treatment for opioid addiction is to find partial opioid agonists with properties of long duration of action and high oral bioavailability. In a search for such compounds, thienorphine, a novel analog of buprenorphine, was synthesized. Here, we reported that, like buprenorphine, thienorphine bound potently and nonselectively to -, ␦-, and -opioid receptors stably expressed in CHO (Chinese hamster ovary) cells and behaved as a partial agonist at -opioid receptor. However, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
31
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 22 publications
10
31
1
Order By: Relevance
“…Consistent with a previous report (Yu et al, 2006), thienorphine bound to -, -, and ␦-opioid receptors. In the previous study, thienorphine produced 62% of maximal stimulation at -receptors (compared with morphine), functioning as a partial -receptor agonist.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with a previous report (Yu et al, 2006), thienorphine bound to -, -, and ␦-opioid receptors. In the previous study, thienorphine produced 62% of maximal stimulation at -receptors (compared with morphine), functioning as a partial -receptor agonist.…”
Section: Discussionsupporting
confidence: 79%
“…1) is a newly synthesized oripavine derivative (Liu et al, 2005) that reportedly binds to -, -, and ␦-opioid receptors in vitro and has good oral bioavailability in mice (Yu et al, 2006). Furthermore, in mice, thienorphine has potent antinociceptive effects that are thought to be mediated by -opioid receptor agonism (Yu et al, 2006); however, the pharmacological (receptor) mechanism(s) underlying the antinociceptive effects of thienorphine has not been confirmed in other species. The current study evaluated the antinociceptive and other behavioral effects of thienorphine in rhesus monkeys and also examined its receptor binding in cell membrane homogenates.…”
mentioning
confidence: 99%
“…As expected, the receptor binding assay revealed that 030418, a novel 6,14-bridged oripavine compound, displayed nonselective binding affinities to the µ-, κ-, and δ-opioid receptors and the ORL1 receptor with K i values in the nanomolar range, as did thienorphine. Moreover, our observation that thienorphine highly bound to the µ-, κ-, and δ-opioid receptors is in accord with previous reports [15,16] . Consistent with Li et al [16] , thienorphine exhibited partial agonist activity at the κ-opioid receptor and at the µ-opioid receptor (to a lesser extent) but not at the δ-opioid receptor in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…experimental data regarding the potency of dihydroetorphine and morphine were consistent with those of Aceto et al [34] . In addition, 030418 had more potent and powerful antinociceptive effects in vivo than its parent compound thienorphine, which has previously been demonstrated to be a partial opioid agonist, with an eD 50 value in the milligram range in the mouse antinociceptive tests [15] . Compared with morphine, 030418 shows a rather long-lasting duration of the antinociceptive effect in the hot-plate test, which is similar to thienorphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation